GAMBARAN TINGKAT PENGETAHUAN AKSEPTOR KB SUNTIK TERHADAP EFEK SAMPING PENGGUNAAN KB SUNTIK 3 BULAN - Wulandari, Amri; Krismiyati, Murti (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2022)
Data Riskesdas in 2018 acceptors who use Kb Milk 4.7%, Injection 1 month 6.1%, IUD 6.6%. PILL 8.5%, Injection 3 months 42.4%. Of these data, acceptors who used 3-month injection contraceptives were the highest. Injectable birth control that can experience side effects such as menstrual pattern disorders, weight gain, headaches and blood pressure increases, lower abdominal pain, hair growth even to a decrease in sexual activity. The purpose of the study in general is to find out an overview of the level of knowledge of injectable birth control acceptors against the side effects of using 3-month injectable birth control. This type of research is descriptive of analytics with a cross sectional approach, the population is the acceptor of 3-Month Injectable Birth Control in The Midwife Independent Practice, Accidental sampling, obtained by 89 respondents, using primary data. Research time from June to December 2021. The results showed that the majority of respondents had sufficient knowledge about the side effects of 3-month injectable birth control as a whole, which was 58.43%. The majority of respondents have sufficient knowledge with the age of > 35 years, namely as much as 40.45%, highly educated 39.32%, employment as an IRT 31.46% and get information sources from health workers, namely as much as 38.20%. We recommend that health workers provide more detailed information related to the side effects of 3-month injectable birth control and its handling. Keywords: Clouding, Acceptor, Side Effects of 3 Months Injectable Birth Control